Point-of-care ultrasound diagnosis of stump appendicitis in the emergency department - Monsomboon, Apichaya (Ultrasound J, 2019)
BACKGROUND: Stump appendicitis (SA) is a rare entity in patients with a history of appendectomy and may result in missed or delayed diagnosis. We report a case of SA diagnosed by emergency department (ED) point-of-care ultrasound (PoCUS) in an elderly woman, thus expediting her care. CASE PRESENTATION: An elderly female patient with a history of appendectomy 27 years ago was referred by her physician to the ED with right lower quadrant pain for 2 days. Using PoCUS the emergency physician identified SA. This was confirmed by computed tomography (CT) scan. The patient was then successfully managed non-operatively using antibiotics. CONCLUSIONS: Despite its rarity, it is feasible to diagnose SA using PoCUS, as patients presenting with right lower quadrant pain and history of appendectomy are at risk for delayed diagnosis, perforation, and poor outcome. PoCUS may reduce time to diagnosis, time to definitive operative or non-operative management, and minimize morbidity.